Neurobrucellosis evaluated by reibergram. A case report - Alberto Juan Dorta Contreras; Cristobal González-Losada; Consuelo Sánchez-Martínez (Universidad de Ciencias Médicas de La Habana, 2018)
Introduction: Brucellosis is a zoonotic and an endemic disease in many areas around the world. The main cause of infection is the intake of unpasteurized milk or the contact with infected animals. Neurobrucellosis includes pathologic conditions in the central and peripheral nervous systems. The main clinical manifestations are meningitis, encephalitis, optical neuritis, and peripheral neuritis. Objective: To evaluate, through reibergram, the intrathecal dynamics of the major immunoglobulin classes and the blood-CSF barrier function in one patient with neurobrucellosis. Case report:  IgA, IgM, IgG and albumin levels in serum and cerebrospinal fluid were quantified by using a radial immunodiffusion technique. Results were placed in the corresponding reibergram. The patient showed evidences of intrathecal synthesis of the three major immunoglobulins without blood-CSF barrier dysfunction. Conclusion: The neuroimmunological study of cerebrospinal fluid can indicate the active course of the intrathecal immune response against this pathogen, where the intrathecal synthesis of immunoglobulins and blood-cerebrospinal fluid barrier function constitute the main markers in the diagnosis of  neuroinflammation. Keywords: Brucellosis, neuroimmunology, neurobrucellosis, neuroinflammation, zoonotic disease, reibergram